ANALISIS PENGARUH KREDIBILITAS INFLUENCER PADA INSTAGRAM TERHADAP MINAT BELI DENGAN KEPERCAYAAN MEREK DAN CITRA MEREK SEBAGAI VARIABEL MEDIASI (Studi pada Perawatan Tubuh Wardah) - Cahyadiningrum, Tri; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Wardah is a beauty company that has various product segments, such as skin care, body care, hair care and makeup. However, even though Wardah's overall sales are number 1 on three online shopping platforms, it turns out that Wardah's products in the body care segment are not even in the top 10 best-selling brands, which indicates the uneven sales of Wardah's body care products both compared to other body care brands and Wardah products in other segments. Therefore, this study aims to examine the effect of Influencer Credibility on Instagram on Purchase Intention, Brand Trust and Brand Image as well as the effect of Brand Trust and Brand Image on Purchase Intention in Wardah Body Care. In other words, Brand Trust and Brand Image have a role as mediating variables. There were 139 respondents used as samples in this study. Respondents who became samples were people who had an interest in buying Wardah products after viewing SMI content on Instagram. The sample collection technique used in this study was non probability sampling with purposive sampling technique and used a questionnaire as a data collection method. Analysis using the Structural Equation Model (SEM) with the AMOS 24 program to test as a whole. The test results show that Influencer Credibility has a positive and significant effect on Brand Trust and Brand Image. Then, Influencer Credibility has a positive but insignificant effect on Purchase Intention. In addition, the results also show that Brand Trust and Brand Image have a positive and significant influence on Purchase Intention.